1997
DOI: 10.1017/s1357729800015538
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immunization against somatostatin and β-agonist administration alone and in combination on growth and carcass composition in young steers

Abstract: The effect of active immunization against somatostatin and ^-agonist administration alone and in combination on growth, carcass composition and endocrine responses was investigated in young steers given a pelleted diet of dried grass and barley (0-7: 0-3) ad libitum for 16 weeks. Immunization alone increased growth rate by proportionately 0-10 but had no effect on plasma growth hormone (GH) or insulin-like growth factor-1 (IGF-1) concentrations (P > 0-10). Carcass protein content was unchanged but fat content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Additionally, Moloney et al (1990) showed an increase in lean and a decrease in fat due to treatment with the βAA L 644,969 . Typically, use of other βAA has not affected carcass ash percentage (Dawson et al, 1997;Schroeder et al, 2003b,c), which is similar to the effect of zilpaterol treatment in the present study. In addition, carcass percentage bone was shown to be decreased in heifers of the present study and by other βAA because of an increase in soft tissue mass (Fabry and Sommer, 1990;Moloney et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, Moloney et al (1990) showed an increase in lean and a decrease in fat due to treatment with the βAA L 644,969 . Typically, use of other βAA has not affected carcass ash percentage (Dawson et al, 1997;Schroeder et al, 2003b,c), which is similar to the effect of zilpaterol treatment in the present study. In addition, carcass percentage bone was shown to be decreased in heifers of the present study and by other βAA because of an increase in soft tissue mass (Fabry and Sommer, 1990;Moloney et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
“…Use of other βAA has resulted in an increase in lean to bone ratio and decreases in lean to fat ratio (Moloney et al, 1990;Dawson et al, 1997). The present study data indicated that zilpaterol is a repartitioning agent, although not as strong as other β 2 -agonists.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The percentage of moisture, protein, ash, and cholesterol in the breast and leg muscles were not affected (p≥0.10) by zilpaterol. Out results are consistent with those of Dawson et al (1997), who supplemented beef steers with other β-AA and did not find any effects on carcass ash percentage.…”
Section: Effect Of Different Zilpaterol Hydrochloride Levels and Feedsupporting
confidence: 90%
“…Many studies have shown that the use of immuno-neutralization against SS could enhance growth in animals (Spencer, 1986;Yun et al, 1996). Immunization against either a chemically synthetic or recombinant SS coupled to a carrier protein has been confirmed to promote the growth rates of immunized animals, including sheep, steers and chickens (Buonomo et al, 1987;Dawson et al, 1997;Shulkes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%